Producción de etanol a partir de cebada no malteada hidrolizada con a y b amilasas comerciales - Herberth Espitia-Rivera; Carolina Espitia-Rocha; Ivonne Gutierrez-Rojas (Universitas Scientiarum)
Ethanol production from hydrolyzed unmalted barley using commercial a- and b-amylase. Objective. To find the optimumconcentration of commercial a- and b-amylase for the obtainment of ethanol from unmalted barley. Materials and methods. Unmaltedbarley was hydrolyzed using various concentrations of commercial a- and b-amylase (Genencor International), following conditionsestablished by the manufacturer. The products of hydrolysis were used as substrates for the production of ethanol by Saccharomycescerevisiae. In addition, a reference assay was performed using malted barley following the conditions established by the distillery.Results. The percentage of starch hydrolysis was 89.4% when adding a-and b-amylase at a concentration of 1 g L-1. Moreover, thisconcentration of amylases yielded a maximum ethanol production (5.02 %) significantly higher than when malted barley was used (3.76%). Conclusions. It was demonstrated that ethanol can be obtained from starch of unmalted barley by adding commercial a- and b-amylase. However, optimization of the process is required due to the higher costs when compared to the traditional process with maltedbarley.